Children, youth and road environment: road traffic accident / Mohamad Ghazali Masuri, Khairil Anuar Md Isa and Mohd Pozi Mohd Tahir - Masuri, Mohamad Ghazali; Md Isa, Khairil Anuar; Mohd Tahir, Mohd Pozi (Universiti Teknologi MARA Cawangan Selangor, 2017)
Driving is a complex process which involves eye-hand-foot coordination. Failure to coordinate will contribute to road traffic accidents (RTA). Young drivers usually represent the highest number of individuals involved in the accident cases. Thus, three common ergonomics principle were examined in this study: human-machine-environment. Issues such as land use, vehicle design and the importance of law enforcement are briefly discussed. Further research is needed to improve driver‟s behavior and responses while driving. Strict enforcement on legislation and early education on road safety are required. It is also suggested that developing country should refer to the preventive model used in developed countries for reference.